Hydrogen Sorption Behavior of the MgH2-Ni Prepared by Reactive Mechanical Alloying - Mustanir, Mustanir; Jalil, Zulkarnain (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2009)
Regarding the use of hydrogen in fuel cell for mobile or stationary applications, metal hydrides can offer a high hydrogen volume capacity and a safe alternative compared with liquid storage or with compressed gas. Among the metal hydrides, magnesium is considered as one of potential hydrogen storage materials because of its high capacity (7.6 wt%), lightweight and low cost. However, high work temperature would slow down kinetics reaction and harden activation process limit practical application of Mg-based hydrides as well. Recently, the high energy ball milling was successfully introduced to prepare hydrogen storage materials. In this work, MgH2 catalyzed with Ni nanoparticles was synthesized by planetary type ball milling under high pressure of hydrogen at 100 bar (10 MPa). As a result, small amount of Ni in nanometer scale acts as a suitable catalyst for kinetics improvement of MgH2 which could absorb 5.3 wt% of hydrogen within 5 minutes at 300ÂºC. It is obvious that small amount Ni (2 mol%) has much better catalyst than catalyst in nanoparticle size; and at the same time, it is allowed to reduce the milling process for short time (2 hours).